An interactive peer-assessment criteria development approach to improving students' art design performance using handheld devices. (July 2015) - Lai, Chiu-Lin; Hwang, Gwo-Jen
Abstract: Engaging students in higher order thinking such as evaluation and analysis has been recognized as being an important strategy for helping them develop knowledge and skills, in particular, in creativeness-oriented learning activities such as artwork design. In this paper, an interactive peer-assessment criteria development approach is proposed to help students develop assessment criteria, learn from viewing peers' work, and make reflections in artwork design activities using mobile devices. To evaluate the effectiveness of the proposed approach, an experiment was conducted in an elementary school art course. A total of 103 students participating in the experiment were assigned to an experimental group and a control group. The students in the experimental group learned with the proposed approach, while those in the control group learned with the conventional peer assessment approach. From the experimental results, it was found that the proposed approach significantly improved the students' learning achievement, learning motivation and meta-cognitive awareness, suggesting the effectiveness of engaging students in assessment criteria development in an interactive manner. Highlights: An interactive peer-assessment criteria development approach is proposed. An experiment was conducted to evaluate the performance of the new approach. The approach has been applied to an elementary school art course. The approach improved the students' learning achievement and leaning motivation. The approach also improved the students' and critical thinking performance.